منهج مركز التطويري لتدريس اللغة الأجنبية بالمدرسة الثانوية "جاء الحق" في تحسين مهارة اللغة العربية - Falahun Niam; M. Hidayaturrahman (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2020)
AbstractThe aim of this research is to determine the curriculum of the Development Center for Teaching Foreign Language in Secondary School. The truth came, whether or not the curriculum fulfills the elements in the curriculum. They are compiled from the first curriculum-making, curriculum objectives, content or study materials, and the teaching and evaluation process. And the type of research in this research is a field research with a qualitative approach of using the curriculum that has been made in the developmental center for foreign language teaching. Data collection is done with observation, interview and documentation. Data analysis uses four stages, which are through data collection, data consolidation, data presentation and conclusion. As for the results of the research, it is an analysis of the curricula of the Development Center for Teaching Foreign Languages in improving the skill of the Arabic language, and showing that the curriculum used has fulfilled the elements of the curriculum, namely the objectives of the curriculum and the content or study materials and the teaching and evaluation process. The teaching process is still not perfect due to the impossibility of time and the curricula are taught differently. As for the inhibiting factors, it is the gathering time because everyone has a busy life, irregularities between the basis and the wishes of the coach. The supporting factors are the support of the curriculum to a large extent by the institution as a trainer for students to speak foreign (Arabic) fluently. So the curriculum has not been completely maximized.